Not Only a Formulation: The Effects of Pickering Emulsion on the Entomopathogenic Action of Metarhizium brunneum - Nitsan Birnbaum; Victoria Reingold; Sabina Matveev; Chandrasekhar Kottakota; Michael Davidovitz; Karthik Ananth Mani; Reut Feldbaum; Noga Yaakov; Guy Mechrez; Dana Ment (Journal of Fungi, 2021)
Growing global population and environmental concerns necessitate the transition from chemical to eco-friendly pest management. Entomopathogenic fungi (EPF) are rising candidates for this task due to their ease of growing, broad host range and unique disease process, allowing EPF to infect hosts directly through its cuticle. However, EPF’s requirement for high humidity negates their integration into conventional agriculture. To mitigate this problem, we formulated Metarhizium brunneum conidia in an oil-in-water Pickering emulsion. Conidia in aqueous and emulsion formulations were sprayed on Ricinus communis leaves, and Spodoptera littoralis larvae were introduced under low or high humidity. The following were examined: conidial dispersion on leaf, larval mortality, conidial acquisition by larvae, effects on larval growth and feeding, and dynamic of disease progression. Emulsion was found to disperse conidia more efficiently and caused two-fold more adhesion of conidia to host cuticle. Mortality from conidia in emulsion was significantly higher than other treatments reaching 86.5% under high humidity. Emulsion was also found to significantly reduce larval growth and feeding, while conferring faster fungal growth in-host. Results suggest that a Pickering emulsion is able to improve physical interactions between the conidia and their surroundings, while weakening the host through a plethora of mechanisms, increasing the chance of an acute infection.